The Effect Of Strenghts-Based Leadership On Work Engagement: The Mediating Role Of Strenghts Use Among Healthcare Professionals - Dwi Adlina Itami Dwi; M. Rasyid Abdillah; Jeni Wardi (International Journal of Health Engineering and Technology, 2026)
In a very competitive business environment, particularly in the healthcare sector, human resources are now among the most crucial aspects influencing an organization's performance. Healthcare employees are required to show the best performance and excellent levels of work engagement to ensure patient safety and the quality of healthcare treatments. According to Schaufeli et al. (2002), work engagement is a positive, rewarding psychological condition characterized by vitality, devotion, and absorption in one's work. 200 responders were chosen through the use of purposeful sampling. Data were gathered by distributing questionnaires, and SEM-PLS was used for analysis. The results show that work engagement is positively and significantly impacted by strengths-based leadership. Furthermore, the use of strengths is positively and significantly impacted by strengths-based leadership, and work engagement is positively and significantly impacted by strengths use. Additionally, the findings show that the relationship between strengths-based leadership and work engagement is positively and significantly mediated by strengths utilization. These results imply that healthcare professionals' work engagement can be improved both directly and indirectly by adopting leadership methods that emphasize identifying and utilizing people' abilities. According to this study, healthcare organizations should encourage strengths-based leadership techniques in order to maximize the potential of healthcare workers, which will improve job engagement and raise the standard of healthcare services.